The Impact of Online Learning on Teachers' Anxiety Levels in the Offline Period (Results of a Survey of PAUD Teachers in Banjarbaru City, South Kalimantan) - Hafidzi, Anwar; Sholihin, Rahmat; Muhdi, Muhdi; Lutfi, Lutfi; Ramli, Muhammad (EDUCATIO : Journal of Education, 2022)
Abstract: This study aims to consider the impact of the pandemic on the teaching-learning process from the perspective of Early Childhood Education (PAUD) teachers. Not many studies have examined the effects of the pandemic on the teaching process with children, even at the PAUD level. This paper aims to gain a deeper understanding of the realization of the teaching and learning process during an emergency due to Covid-19 in Banjarbaru City, which came as a consequence of an unfavorable epidemiological situation. Teachers, children, and parents are recognized in this paper as the main determinants of the quality of education. The results of the attitude assessment of 40 teachers in the city of Banjarbaru there are important aspects of the educational process during an emergency. The data takes place, based on the results obtained, it can be concluded that the level of adaptability of teachers is considered capable enough to deal with new situations and is decreasing as it continues to be extended. face-to-face learning emergency. The results explain a high positive attitude in terms of cooperation between teachers and parents, which indicates that there is a lot of room to improve the quality of education in the future through blended learning. Keywords: Impact, education, children, Covid-19, Banjarbaru.